2016
DOI: 10.1021/jacs.6b05243
|View full text |Cite
|
Sign up to set email alerts
|

Activation of H2 over the Ru−Zn Bond in the Transition Metal−Lewis Acid Heterobimetallic Species [Ru(IPr)2(CO)ZnEt]+

Abstract: Through a dramatic advance in the coordination chemistry of the zinc-hydride bond, we describe the trajectory for the approach of this bond to transition metals. The dynamic reaction coordinate was interrogated through analysis of a series of solid state structures and is one in which the TM-H-Zn angle becomes increasingly acute as the TM-Zn distance decreases. Parallels may be drawn with the oxidative addition of boron-hydrogen and silicon-hydrogen bonds to transition metal centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
61
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 57 publications
2
61
0
Order By: Relevance
“…4 ]. [375] [374] Furthermore,t he reaction of [Ru(IPr) 2 (CO)H] + with Et 2 Zn proceeds via alkane elimination to yield [Ru(IPr) 2 -(CO)ZnEt] + ,w hich features an unusual unsupported RuÀ Zn bond, across which dihydrogen can be activated to form the dihydrogen dihydride complex [Ru(IPr) 2 (CO)( h 2 -H 2 )-(H 2 )ZnEt] + .…”
Section: Transition-metal Complexes Supported By Wcasmentioning
confidence: 99%
“…4 ]. [375] [374] Furthermore,t he reaction of [Ru(IPr) 2 (CO)H] + with Et 2 Zn proceeds via alkane elimination to yield [Ru(IPr) 2 -(CO)ZnEt] + ,w hich features an unusual unsupported RuÀ Zn bond, across which dihydrogen can be activated to form the dihydrogen dihydride complex [Ru(IPr) 2 (CO)( h 2 -H 2 )-(H 2 )ZnEt] + .…”
Section: Transition-metal Complexes Supported By Wcasmentioning
confidence: 99%
“…[5] The proposition that these species could dimerize by 3-center 2-electron bonds seeded ideas that ultimately led to the discovery of dihydrogen complexes. [6] A handful of heterobimetallic complexes containing transition metal and zinc centers bridged by hydride ligands are known, [7][8][9][10][11][12][13][14] The majority however, include more than one bridging hydride ligand clouding analysis of the TM-H-Zn group. Through kinetic protection of a zinc center with a sterically demanding ligand, we recently isolated a rare example of a heterobimetallic complex possessing an unsupported Cu-H-Zn moiety.…”
mentioning
confidence: 99%
“…[6] Ah andful of heterobimetallic complexes containing transition metal and zinc centers bridged by hydride ligands are known. [7][8][9][10][11][12][13][14][15] Themajority however, include more than one bridging hydride ligand clouding analysis of the TM-H-Zn group.T hrough kinetic protection of az inc center with asterically demanding ligand, we recently isolated ar are example of ah eterobimetallic complex possessing an unsupported Cu-H-Zn moiety. [15c] Here we describe an advance in the coordination chemistry of the zinc-hydride bond to transition metals.Through analysis of aseries of solid state structures and calculations,w ed escribe the reaction trajectory for the approach of as ingle zinc-hydride bond to atransition metal.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative approachi st os trip away the scaffold to leave two coordinatively unsaturated metals held together by an "unsupported" bond. [10] This readily adds H 2 across the RuÀZn bond to give 3.D FT calculations showed that the Zn centre acts as ar eversibleh ydride acceptor that participates directly in bond cleavage. [10] This readily adds H 2 across the RuÀZn bond to give 3.D FT calculations showed that the Zn centre acts as ar eversibleh ydride acceptor that participates directly in bond cleavage.…”
Section: Introductionmentioning
confidence: 99%